Characterizing Exclusively Breastfed Infant Stool via a Novel Infant Stool Scale. (29th October 2018) - Gustin, Jennifer; Gibb, Roger; Kenneally, Dianna; Kutay, Ben; Waimin Siu, Susana; Roe, Don
Abstract: Analysis of stool has long been a diagnostic tool across a number of disease states. Currently, there are two stool scales in clinical use, the Bristol Stool Scale and the Amsterdam Infant Stool Scale. However, the existing categorizations for stool may not sufficiently cover the broad range of stool output for exclusively breastfed infants. The Bristol Stool Scale is not age specific to cover children who are not toilet trained and the Amsterdam Infant Stool Scale, though developed for children who are not toilet trained, does not sufficiently cover the wide variety of consistencies of exclusively breastfed infant stools. Through a robust understanding of exclusively breastfed infant stool characteristics, a new stool scale has been developed. It is proposed that this stool scale may better assist in observing and recording exclusively breastfed infant stool in a more accurate manner, which may aid in diagnostic capabilities.